Rwanda’s involvement in Eastern DRC: a criminal real options approach - Cassimon, Danny (Crime, law and social change, 2013)
This paper applies an alternative model to analyze criminal behaviour by countries based on real option models. Criminal options incorporate a richer framework than traditional cost-benefit models and allow examining the optimal timing of a crime as criminals have the possibility but not the obligation to commit a crime in the near future. From the model, we show how criminal states can actively manage their criminal options. More importantly, we show how the international community can optimally intervene pro-actively, by reducing the incentives for criminal states to execute their criminal options. These novel insights are then applied to two episodes of criminal behaviour by Rwanda in the Democratic Republic of Congo (DRC): the massive killing of Hutu refugees by the Rwanda Patriotic Army (RPA) in late 1996-early 1997 and the illegal exploitation of Congolese resources from August 1998 onwards. This article describes and assesses these activities from this real option perspective.